Emotional Accounting: Uncovering the Role of Affect in Managerial Decision Making - Tania, Tania; Ruslim, Herman (Dhana, 2025)
This study examines the role of emotions and emotional intelligence in managerial decision-making, focusing on how affect influences performance and decision quality. Managerial decision-making is not only driven by data and rational analysis but also influenced by emotional elements that interact with rational evaluation. The study found that emotions can enrich the decision-making process, especially in situations of uncertainty or crisis. Emotional intelligence plays a crucial role in helping managers manage their own and others' emotions, and influences interpersonal relationships, ultimately improving managerial performance. However, the study also highlights psychological biases that can influence rational judgment and lead to suboptimal decisions. Conversely, an organizational culture that supports acceptance of emotions can improve decision-making quality and enhance well-being in the workplace. The study also suggests the need for technology integration, such as artificial intelligence, that must balance emotional considerations in the decision-making process. This research contributes to the development of the concept of emotional accounting, which combines behavioral economics and psychology in managerial decision-making.